A review on the sensing mechanisms and recent developments on metal halide-based perovskite gas sensors. Issue 28 (5th July 2022) - Shinde, Pratik V.; Patra, Abhinandan; Rout, Chandra Sekhar
Abstract : This review provides a brief overview of the progress regarding the research developments, present status, and future outlooks of metal halide perovskite-based gas sensors. Abstract : Currently, halide perovskites have attracted increasing attention for gas sensing applications owing to their unique structural and optoelectronic properties. This review provides a brief overview of the progress regarding the research developments, present status, and future outlooks of metal halide perovskite-based gas sensors. Initially, we describe the optoelectronic, magnetic, and catalytic properties of this family of materials. The synthetic protocols for halide perovskites are comprehensively discussed with a major focus on their various synthetic techniques. Subsequently, we elucidate the mechanism of chemiresistive and optical property-dependent and capacitive-type gas sensors. Further, we present the state-of-the-art progress on self-powered gas sensors and sensors based on a change in the optical, electrical and capacitance properties of halide perovskites. Finally, we conclude with the current status in this field, highlighting some challenges and future perspectives for further studies.